A few remarks on the stochastic structure of the unemployment rate in Poland by gender - Jaworski, Stanisław (Kilka uwag o stochastycznej strukturze stopy bezrobocia w Polsce według płci, 2020)
The quarterly unemployment rate from the Labour Force Survey covering Poland’s data from the first quarter 2005 to the third quarter 2019 was investigated. The issue was to reveal its stochastic structure as a trend, seasonality and disturbance and to make a prognosis. The analysed data comes from a survey based on rotational design, so the problem of possibly autocorrelated survey errors was taken into consideration. Following Harvey (2000), Pfeffermann, Feder, and Signorelli (1997), Yu and Mantel (1997) and Bell and Carolan (1998) it seemed to be of great importance to include the proper autocorrelation structure of the errors into a statistical treatment. It appeared that for Polish unemployment data that structure was not as it could have been expected. After the model was fitted to the data, a conclusion about the specificity of the unemployment rate with respect to gender was drawn. Unemployment forecast until 2020:Q4 is provided
Econometrics = Ekonometria, 2020, Vol. 24, No. 2, s. 41-52
Keywords: unemployment rate; rotational design; structural time series; poziom bezrobocia; plany rotacyjne; strukturalne szeregi czasowe